Outbound supply chain collaboration modelling based on the automotive industry - Vilkelis, Aurimas; Jakovlev, Sergej (Transport, 2014)
The global financial crisis has highlighted shortcomings of logistics operations of many manufacturers. In Europe, the largest share of cargo is transported by road transport, where empty running accounts for about 27%. The statistical result reflects the inefficient use of transportation resources. Today it may be difficult to imagine the whole distribution chain of automobiles manufactured in Europe that would integrate all manufacturers. Nevertheless, in an effort to diminish the shortcomings of transport operations, automotive manufacturers and Logistics Service Providers (LSP) should pay more attention to logistics cooperation. The article presents the specific features of distribution networks of vehicles manufactured in Europe, also providing a scenario of integrating finished vehicle output of different vehicle manufacturers in a single distribution network. The demand for transport resources and efficiency of use of the resources was established according to the scenario. This article is a contribution and a fresh look at the variety of the solutions of transportation problems in modern European automotive industry.First published online: 22 May 2013